Effects of maternal age on the expression of mesenchymal stem cell markers in the components of human umbilical cord - Alrefaei, Ghadeer I.; Ayuob, Nasra N.; Ali, Soad S.; Al-Karim, Saleh (Folia histochemica et cytobiologica, 2015)
Although the human umbilical cord (UC) has been previously considered a medical waste, its use as a main source of fetal stem cells for regenerative medicine applications has increased over the past few years. The aim of the study was to assess the impact of the maternal age on the expression of mesenchymal stem cells (MSC) markers CD105 and CD29 in the different areas of human UC. In this comparative cross sectional study, one hundred term UCs from five maternal age groups (20-45 years) were collected after delivery from healthy mothers and were processed to assess both immuno- and gene expression of CD105 and CD29 surface antigen markers using immunohistochemical and RT-PCR techniques. The immunoexpression of CD105 and CD29 in the amniotic membrane (AM) and Wharton's jelly (WJ), the umbilical artery (UA) and the umbilical vein (UV) showed significant negative correlation with the maternal age (p < 0.001). Reduced amount of cells as well as the studied MSC markers and their gene expression levels were documented in older age mothers. CD105-positive MSCs were more abundant in the UA, whereas CD29-positive MSCs were more abundant in the AM and WJ. The decreased expression of CD105 and CD29 MSCs markers with age suggests that selective isolation of MSCs from Wharton's jelly, umbilical artery or umbilical vein of younger mothers should be recommended.